EFFECT OF IRRIGATION SCHEDULES AND PLANTING METHODS TION SCHEDULES AND PLANTING METHODS ON YIELD AND WATER USE EFFICIENCY OF OKRA UNDER RICERAI-OKRA CROPPING SYSTEM - KUMAR SINGH, RAHUL; PRATAP, TEJ; SINGH, VED PRAKASH; PRAKASH SINGH, NAVEEN (The Bioscan, 2016)
An experiment was conducted during summer season 2011 at Agronomy Research Farm of Narendra Deva University of Agriculture and Technology, Kumarganj, Faizabad (U.P.) to evaluate the effect of Irrigation Schedules and Planting Methods on okra. The experiment was laid out in split-plot design with four replications, assigning 12 treatments consisting 4 irrigation schedules and 3planting methods. The results revealed that different irrigation schedules and planting methods significantly influenced the growth, yield and water use efficiency of okra. Irrigation schedule at five days interval recorded Thehighest plant height (80.20 cm),dry matter accumulation plant-1 (44.33g), No. of picking plant-1 (11.00), No. of fruits plant-1(17.00), Total yield plant-1 (188.38), Yield ha-1 (9516 kg) and Water use efficiency (96.50 kg/ha/cm). In case of planting methods Raised bed sowing method significantly proved best than others with the maximum plant height (82.11 cm), dry matter accumulation plant-1 (42.98g), No. of picking plant-1(11.00), No. of fruits plant-1(17.25), Total yield plant-1 (192.73g), Yield ha-1 (9735kg) and Water use efficiency (95.46 kg/ha/cm). On the basis of the above summarized results okra growers can adopt the 5 day interval irrigation schedule and raised bed method of planting for higher yield of okra and efficient use of water.